Changing the focus: The need for cross-scale dynamic management in the Southern Ocean and implications for holistic conservation of Antarctic marine living resources - Zaldúa, Natalia (2024)
The Convention on the Conservation of Antarctic Marine Living Resources (CCAMLR) establishes the regulatory framework for fisheries management and the establishment of Marine Protected Areas (MPA) in the Southern Ocean. Identifying foraging areas regularly used by penguins provides valuable information for the small-scale management of the krill fishery and the design of MPAs, currently under discussion in CCAMLR. We used geolocators to identify the areas used by Ad´elie penguins from Ardley Island (South Shetlands Islands) during the non-breeding season and Stable Isotope Analysis (SIA) (δ13 C and δ15 N) on feathers to study the trophic niche. Ad´elie penguins depended on resources available in CCAMLR subareas 48.1 and 48.5 during the post-breeding and molting stage, the subarea 48.5 during the post-molting stage and subareas 48.1, 48.2 and 48.5 during the pre-breeding stage, critical moments of the species’ annual cycle. The Domain 1, Weddell Sea and SOISS MPA proposal areas were extensively used. SIA results show the use of coastal and off-shore foraging areas in 2022, but principally off-shore areas in 2021. Ad´elie penguins dependence on resources from different subareas in different times of the year emphasizes the need of incorporating the temporal dimension of resources utilization when designing conservation measures in the Southern Ocean. With an increasing pressure on Ad´elie penguin colonies in the western Antarctic Peninsula, its long-term protection might depend on both 1) well designed and managed MPAs in the Domain 1 and the Weddell Sea, and 2) small-scale fisheries management that simulta neously consider activities undertaken in different small-scale management units.